Editorial. Issue 2 (1st June 2019) - Welch, Penny; Wright, Susan
Abstract : In this issue of Learning and Teaching: The International Journal of Higher Education in the Social Sciences, academics from Denmark, Chile, the United States and the United Kingdom analyse capacity-building projects between European and African universities, the experiences of mobile academics returning to their home country, the role of tutors on international interdisciplinary MA programmes, the contemporary relevance of classical and medieval approaches to education and levels of information literacy among undergraduates.